2014
DOI: 10.3168/jds.2014-7912
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antibacterial activities of exopolysaccharides from Bifidobacterium bifidum WBIN03 and Lactobacillus plantarum R315

Abstract: The objective of this study was to investigate the antioxidant and antibacterial activities of exopolysaccharide (EPS) from Bifidobacterium bifidum WBIN03 (B-EPS) and Lactobacillus plantarum R315 (L-EPS). The 1,1-diphenyl-2-picrylhydrazyl (DPPH)-radical scavenging, hydroxyl radical-scavenging, and superoxide radical-scavenging abilities were measured to evaluate antioxidant activity. Inhibition of erythrocyte hemolysis and lipid peroxidation was also measured. Both B-EPS and L-EPS had strong scavenging ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(100 citation statements)
references
References 32 publications
1
90
0
2
Order By: Relevance
“…A moderate antioxidant activity of methanol extract of exopolysaccharide from Cyanobacterium Arthrospira platensis using the Trolox Equivalent Antioxidant Activity assay was determined by Challouf et al (2011) [11]. A strong scavenging ability of exopolysaccharide from Bifidobacterium bifidum WBIN03 and Lactobacillus plantarum R315 was observed against DPPH and superoxide radicals at high concentration [15]. The EPS produced by Lactobacillus plantarum YW32 at a dose of 5mg/ml had strong scavenging abilities toward hydroxyl and superoxide radicals [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A moderate antioxidant activity of methanol extract of exopolysaccharide from Cyanobacterium Arthrospira platensis using the Trolox Equivalent Antioxidant Activity assay was determined by Challouf et al (2011) [11]. A strong scavenging ability of exopolysaccharide from Bifidobacterium bifidum WBIN03 and Lactobacillus plantarum R315 was observed against DPPH and superoxide radicals at high concentration [15]. The EPS produced by Lactobacillus plantarum YW32 at a dose of 5mg/ml had strong scavenging abilities toward hydroxyl and superoxide radicals [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that microbial polysaccharides act as an effective antioxidant [ 25,15,17,24], but very limited information is available on the antioxidant mechanisms of the exopolysaccharides action at molecular level [6,26].…”
Section: Discussionmentioning
confidence: 99%
“…9, No. 2; other studies against human bacteria (Li et al, 2014;Roselló et al, 2013). Therefore, it is suggested that the EPS could have acted against the pathogen through the activation of resistance mechanisms in tomato plants, even with the plant protection occurring in a short interval between EPS application and the inoculation of the plants (3 days), and the lacking of bacterial spot control when applied 7 days before the treatment.…”
Section: Characmentioning
confidence: 99%
“…Study by Li., et al [19] reported that exopolysaccharides from Bifidobacterium bifidum WBIN03 and Lactobacillus plantarum R315 exhibited an- The efficiency to produce EPS by bacterial strain is also crucial, if the EPS is to be produced at industrial scale due to its significant use. Our results were found comparable and better as compared to earlier report which suggested to recover bacterial EPS from basal medium was 90.66 ± 16.8 mg/100 ml of dry weight [23], whereas the present study recovered 259 and 312 mg/100 ml of EPS from the isolates KPEP3 and KPEP4 respectively indicating the potent EPS producers have been isolated in the present study.…”
Section: Phenotypic and Biochemical Characterization Of The Epsproducmentioning
confidence: 99%